2023
DOI: 10.1038/s41419-023-05961-3
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT, a novel immune checkpoint therapy for melanoma

Abstract: Melanoma is the most aggressive and deadliest type of skin cancer. In the last 10 years, immune checkpoint blockades (ICBs) including PD-1/PD-L1 and CTLA-4 inhibitor has been shown to be effective against melanoma. PD-1/PD-L1 and CTLA-4 inhibitors have shown varying degrees of drug resistance in the treatment of melanoma patients. Furthermore, the clinical benefits of ICBs are also accompanied by severe immune toxicity. Therefore, there is an urgent need to develop new immune checkpoint inhibitors to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Tyrosine-based inhibition motif domain (TIGIT) is an important immune checkpoint for T/NK cells 25 . It has been found that TIGIT can be detected at breast cancer 26 , renal cell carcinoma 27 , lung adenocarcinoma 28 , hepatocellular carcinoma 29 , gastric cancer 30 , acute myeloid leukemia 31 , melanoma 32 and promote tumor onset, progression and prognosis 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine-based inhibition motif domain (TIGIT) is an important immune checkpoint for T/NK cells 25 . It has been found that TIGIT can be detected at breast cancer 26 , renal cell carcinoma 27 , lung adenocarcinoma 28 , hepatocellular carcinoma 29 , gastric cancer 30 , acute myeloid leukemia 31 , melanoma 32 and promote tumor onset, progression and prognosis 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…TIGIT, also known as WUCAM, VSTM3 and VSIG9, is identified in 2009 as a co-inhibitory receptor belonging to the immunoglobulin superfamily which consists of an extracellular domain harboring an immunoglobulin variable region (IgV) linked to a type 1 transmembrane domain, and an intracellular domain containing an immunoreceptor tyrosine-based inhibitory motif (ITIM) and an Ig tail-tyrosine (ITT)-like motif constitute ( 94 ). Activated CD4+ and effector CD8+ T cells and NK cells express TIGIT on the cell surface, which interacts with the poliovirus receptor (PVR, also known as CD155) with high affinity and with poliovirus receptor-related 2 (PVRL2, also known as CD112) with lower affinity ( 64 ).…”
Section: Immune Checkpoints In Cancer Therapymentioning
confidence: 99%
“…T-cell immunoreceptors with immunoglobulin and the immunoreceptor tyrosinebased inhibition motif domain (TIGIT) and its ligand CD155 are also being explored as a new immune checkpoint target for their role in delivery inhibition signals to T cells, NK cells, and regulatory T cells [100]. TIGIT expression can be closely associated with melanoma occurrence, development, and prognosis; consequently, decreased TIGIT expression is associated with inhibited tumor growth in melanoma patients.…”
Section: Immune Checkpoint Inhibitors (Icis)mentioning
confidence: 99%